2012
DOI: 10.1017/s1368980012005307
|View full text |Cite
|
Sign up to set email alerts
|

Calcium intake and osteoporosis: the influence of calcium intake from dairy products on hip bone mineral density and fracture incidence – a population-based study in women over 55 years of age

Abstract: Objective: The incidence of osteoporosis increases with age and is most frequently observed in postmenopausal women. The objective of the present populationbased cohort study was to assess the influence of Ca intake from dairy sources on hip bone mineral density and hip fracture incidence in a group of Polish women over 55 years of age. Design: The main outcome measures included: bone mineral density, the number of previous fractures and the reported Ca intake from dairy sources, assessed by a diet questionnai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
40
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 36 publications
5
40
2
Order By: Relevance
“…The average calcium intake from total dairy products in analyzed subjects was 788.66mg/day, and dietary calcium intake was 818.41 mg/day; findings from this study are fully consistent with results from Sahni S et al (4) and from Gariguet D (22), and partially consistent with results from Fan T et al (23) in terms of reporting relatively high average of calcium intakes (829 mg/day and 751mg/day and 1239 mg/day, respectively). However, in contrast to our study, results from two Polish studies conducted by Wadalowska L et al (9) and Włodarek D et al (12) found relatively low calcium intake from dairy products in women (375 mg/day and 424.7 mg/day, respectively). Similarly, a Korean study conducted by Kim SH et al [11] and a Brazilian study conducted by Harter DL et al (15) found low average calcium consumption of 547.9mg/day and 418.7 mg/day, respectively.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The average calcium intake from total dairy products in analyzed subjects was 788.66mg/day, and dietary calcium intake was 818.41 mg/day; findings from this study are fully consistent with results from Sahni S et al (4) and from Gariguet D (22), and partially consistent with results from Fan T et al (23) in terms of reporting relatively high average of calcium intakes (829 mg/day and 751mg/day and 1239 mg/day, respectively). However, in contrast to our study, results from two Polish studies conducted by Wadalowska L et al (9) and Włodarek D et al (12) found relatively low calcium intake from dairy products in women (375 mg/day and 424.7 mg/day, respectively). Similarly, a Korean study conducted by Kim SH et al [11] and a Brazilian study conducted by Harter DL et al (15) found low average calcium consumption of 547.9mg/day and 418.7 mg/day, respectively.…”
Section: Discussioncontrasting
confidence: 99%
“…These results fully support the results of Fardellou P et al (24) and partially support those of Włodarek D et al (12) who reported no significant difference in respect to total hip BMD T-scores, but reported significant association of higher calcium intake with femoral neck BMD T-score that was not included in our analysis. However, upper BMD tertile in our study had significantly higher average dairy and dietary calcium intake than middle or bottom BMD tertiles (p<0.05; Table 3).…”
Section: Discussionsupporting
confidence: 92%
“…9,[25][26][27] In keeping with DGA goals for a foodbased approach to a nutritionally adequate U.S. diet, 1 this analysis indicates that consuming recommended amounts of dairy by itself has the potential to reduce inadequate calcium intake in all agegender groups (Table III). Dietary supplements play a role in helping some population groups get more calcium, with the largest impact in older men (71+ years) and women (51+ years), however about half of these adults are still consuming below the EAR (Table IV).…”
Section: Other Vitamins and Mineralsmentioning
confidence: 94%
“…The baseline epidemiology data from the RAC-OST-POL study were described previously [9], and in other manuscripts, some aspects including nutrition [10], functional status [11], and the role of education, marital status, occupation or residence [12] were presented.…”
Section: Methodsmentioning
confidence: 99%